Hyperproduction of Alpha-Hemolysin in a sigB Mutant Is Associated with Elevated SarA Expression in Staphylococcus aureus - Cheung, Ambrose L. (American Society for Microbiology, 1999)
To evaluate the role of SigB in modulating the expression of virulence determinants in Staphylococcus aureus, we constructed a sigB mutant of RN6390, a prototypic S. aureus strain. The mutation in the sigB gene was confirmed by the absence of the SigB protein in the mutant on an immunoblot as well as the failure of the mutant to activate ςB-dependent promoters (e.g., the sarC promoter) of S. aureus. Phenotypic analysis indicated that both alpha-hemolysin level and fibrinogen-binding capacity were up-regulated in the mutant strain compared with the parental strain. The increase in fibrinogen-binding capacity correlated with enhanced expression of clumping factor and coagulase on immunoblots. The effect of the sigB mutation on the enhanced expression of the alpha-hemolysin gene (hla) was primarily transcriptional. Upon complementation with a plasmid containing the sigB gene, hla expression returned to near parental levels in the mutant. Detailed immunoblot analysis as well as a competitive enzyme-linked immunosorbent assay of the cell extract of the sigB mutant with anti-SarA monoclonal antibody 1D1 revealed that the expression of SarA was higher in the mutant than in the parental control. Despite an elevated SarA level, the transcription of RNAII and RNAIII of the agr locus remained unaltered in the sigB mutant. Because of a lack of perturbation in agr, we hypothesize that inactivation of sigB leads to increased expression of SarA which, in turn, modulates target genes via an agr-independent but SarA-dependent pathway.